Dinâmica folicular ovariana e bases para a aplicação das biotécnicas da reprodução em bovinos - Rodrigues, Tito Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
In the last years Brazil has achieved a leading position in worldwide cattle breeding. This country is consolidating the practice of an intensive and technical level cattle breeding, due to greater emphasis on reproductive efficiency and genetic improvement. The attention given to reproductive efficiency became to enhance the genetic improvement process, by exploiting the full reproductive potential of the animals. The biotechniques applied to reproduction arised to expand the reproductive potential for greater economic return. Are the most important reproductive biotechniques the FTAI and in vivo and in vitro embryo production for embryo transfer. Different hormonal treatments are consolidating to interfere with normal physiology in order to achieve the desired goals. The FTAI works to increase the reproductive rates of cattle through pre-booked artificial insemination in all the females in reproduction, without the need for estrous detection. The in vivo and in vitro embryo production aims to distribute the genetics of males and females genetically improved by transferring their embryos to genetically inferior females. Superovulation treatments designed to prevent the mechanism of dominance, which results in many follicles ovulating simultaneously for in vivo embryo production. To the in vitro embryo production, the technique of ovarian puncture guided by transvaginal ultrasound allows to aspirate a number of quality oocytes. The application of biotech is based on knowledge of the female and ovarian reproductive physiology and knowledge of their acting in different breeds and environments.

Nos últimos anos o Brasil atingiu uma posição de destaque na pecuária bovina mundial. Neste país vem se consolidando a prática da bovinocultura intensiva e tecnificada, graças ao maior destaque dado à eficiência reprodutiva e ao melhoramento genético. A atenção dada à eficiência reprodutiva visa intensificar o processo de melhoramento genético explorando todo o potencial reprodutivo dos animais. As biotécnicas aplicadas à reprodução surgiram para ampliar esse potencial reprodutivo, visando maior retorno econômico. Destacamse as biotécnicas da IATF e produção in vivo e in vitro de embriões para transferência de embriões. São utilizados diferentes tratamentos hormonais para interferir na fisiologia normal a fim de atingir os objetivos desejados. A IATF visa aumentar os índices reprodutivos do rebanho através da inseminação préagendada de todas as fêmeas em reprodução, sem a necessidade da observação de cio. Já a produção in vivo e in vitro de embriões visa distribuir a genética de machos e fêmeas melhorados, transferindo seus embriões para fêmeas geneticamente inferiores. Os tratamentos superovulatórios visam impedir o mecanismo da dominância, fazendo com que vários folículos ovulem simultaneamente, para produção in vivo dos embriões. Já a técnica da punção ovariana transvaginal guiada por ultrassom permite a aspiração segura de oócitos de qualidade para produção in vitro. A aplicação dessas biotécnicas se baseia no conhecimento da fisiologia reprodutiva e ovariana das fêmeas e no conhecimento do seu comportamento em diferentes raças e ambientes.
Keywords: Bovino - Reprodução; Biotecnologia animal - Reprodução; Bovino - Tratamentos hormonais; Bovine - Reproduction